Parenting with Patience: Parental Incentives and Child Development - Daniela Del Boca; Christopher Flinn; Ewout Verriest; Matthew Wiswall (Institute of Labor Economics (IZA), 2023)
We construct a dynamic model of child development where forward-looking parents and children jointly take actions to increase the child's cognitive and non-cognitive skills within a Markov Perfect Equilibrium framework. In addition to time and money investments in their child, parents also choose whether to use explicit incentives to increase the child's self-investment, which may reduce the child's future intrinsic motivation to invest by reducing the child's discount factor. We use the estimated model parameters to show that the use of extrinsic motivation has large costs in terms of the child's future incentives to invest in themselves.
Keywords: J13; D1; 330; time allocation; child development; parenting styles